(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the process of updating the theoretical foundations for designing environmental education at various stages. Greening education is viewed as a system-forming element of environmental education, which will enable the full use of environmental, pedagogical, and psychological principles and patterns of developing environmental competence and environmental culture in modern schoolchildren, consistent with sustainable development goals.